Sistem Integrasi Koagulasi dan Adsorpsi dalam Reduksi Logam Berat (Cr6+ dan Cu2+) pada Limbah Cair Industri Tekstil - Judy RB Witono (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The activated sludge method is the mostly method used in textile industry wastewater treatment. This method can not eliminate the heavy metal ion, needs a huge area and skillfull operators. Therefore, this research will developed a physical and chemical integration method, i.e. coagulation method (with alum and FeSO4) and adsorption method (with activated fly ash). In this research we used an artificial wastewater contains metal salt solution of Cr(VI) and Cu(II). Fly ash adsorbent were made by carbonization at temperature 400oC and 600oC in 1 hour, and activated with 12M, 9M and 6M HCl and NaOH. The variable observed in the coagulation method was the mass ratio of alum : FeSO4 (1:0; 1:1; 0:1). The performance of the system was measured based on the concentration reduction of Cr(VI) and Cu(II) by spectrophotometry.The best adsorbent for Cr(VI) is fly ash which carbonized at 600°C and activated by 12 M HCl (49.48% reduction), while for Cu(II) is at 400°C and 12 M NaOH (91.16% reduction). The best coagulant for Cr(VI) is FeSO4 (28.21% reduction), while for Cu is a mixture of alum:FeSO4 (75.83% reduction). The integration of coagulation-adsorption process is suitable only for reducing ion Cu2+ (99.72%).